NON PHARMACOLOGICAL APPROACHES IN THE MANAGEMENT OF DIABETES MELLITUS - RAMAM SRIPADA,; HEMANTH KUMAR VANGALA,; SUDEEPTHI PADALA,; DASARATHA DHANARAJU MAGHARLA, (Asian Journal of Pharmaceutical and Clinical Research, 2019)
Diabetes can be defined as a metabolic disorder characterized by resistance to the action of insulin, insufficient insulin secretion, or both. In this article, we reviewed about the non-pharmacological approaches in the management of diabetes mellitus that includes diet and stress management programs such as Pranayama, meditation, and exercises along with the lifestyle modification which has to be followed by the diabetics for the better management of diabetes in natural ways. By following, these approaches besides regular usage of medications one can lead a healthy life with very less complications. The quality of life can be increased in the patients who follow these methods when compared to those patients who do not consider any of these methods in their daily life. Not only the patient, a healthy individual but can also prefer these methods to prevent chronic diseases and make their day to day life happy and healthy.